Advances in the pathophysiology and treatment of heart failure with preserved ejection fraction. (May 2015) - Tannenbaum, Sara; Sayer, Gabriel T.
Abstract : Purpose of review: With the failure of multiple trials to identify a successful therapy for heart failure with preserved ejection fraction (HFpEF), attention has shifted to defining specific phenotypes within the HFpEF spectrum in an effort to develop a targeted approach to treatment. Here we summarize the most recent studies investigating the pathophysiology and clinical features of HFpEF, and discuss recent clinical trials in the context of developing treatments that look toward the underlying cause of this disorder. Recent findings: Advances in basic science and clinical research have further characterized HFpEF, identifying multiple pathophysiological mechanisms that ultimately lead to exercise intolerance and volume overload. The success of small studies focused on specific subsets of the HFpEF population has promoted the concept that there may not be one treatment strategy that can universally be applied to HFpEF. Summary: HFpEF is associated with significant morbidity and mortality and accounts for approximately half of patients with chronic heart failure. HFpEF is a complex disease, encompassing a diverse cohort of patients and marked by the presence of multiple etiological mechanisms. The failure to develop successful therapies for the management of HFpEF may be because of inadequate standardization of the HFpEF diagnosis, overly broad inclusion criteria and inadequate differentiation of disease subtypes. Given the heterogeneity among patients with HFpEF, much of the current research is focused on understanding of pathophysiology and identifying disease phenotypes that may respond to a targeted treatment approach. Several newer approaches, including neprilysin inhibition and device therapy, offer promise for a new era of HFpEF treatment.